Risk behaviours of homeless people who inject drugs during an outbreak of hepatitis C, Northern Ireland, 2016‐2017. Issue 12 (18th August 2019) - Maisa, Anna; Semple, Susan; Griffiths, Alison; Ngui, Siew Lin; Verlander, Neville Q.; McCaughey, Conall; Doherty, Lorraine; Jessop, Lucy; ,
Abstract: From July to August 2016, 4 homeless people who injected drugs (PWID) with acute or recent hepatitis C virus (HCV) infection were reported in Belfast. A multidisciplinary team including public health, homeless and addiction services undertook an investigation to identify risk behaviours and interrupt transmission chains. Recent HCV cases were defined as negative test within the previous year, or reported injecting for less than 1 year; acute cases had tested negative within the previous 6 months. Contacts in the injecting networks of cases were identified for testing. We undertook a cross‐sectional survey using structured questionnaires to elicit risk behaviours for PWID and compare behaviours between self‐reported hepatitis C positive and negative subjects. During the outbreak investigation until December 2017, 156 PWID were tested and 45 (29%) cases identified, including 7 (16%) recent and 13 (29%) acute infections. 68 PWID, including 12 cases, were interviewed. All respondents reported using heroin, with 76% injecting once or more daily. Sharing was reported for spoons (58%) and filters (53%), but also needles (27%) and syringes (29%). Hepatitis C positive individuals had higher odds to be injecting in public toilets (AOR 17, 95% CI 0.71‐400, P  < .05) when compared with hepatitis C negative individuals. Hepatitis C positive individuals were more likely to inject in public spaces, but all respondents indicated concerning risk behaviours. We recommend active surveillance with ongoing testing, expanding existing harm reduction programmes and access to bespoke services.